Studi Simulasi Optimasi Parameter Proses Implantasi ION Nitrogen Multi Energi ke Dalam Permukaan SS 316L Menggunakan Program SRIM - Haerul Ahmadi; B. A. Tjipto Sujitno; Yudithia Balo Tarigas; Andi Rosman N. (Journal of Engineering Science and Technology, 2023)
Nitrogen ion implantation at 50 keV of energy on the surface of SS 316 stainless steel, by calculation will only be able to reach a depth of 561 Å and the ions will be distributed Gaussian effectively at a depth of 561 Å ± 339 Å, so that from the surface to a depth of 222 Å is not filled by ions (empty) which of course will affect the properties of the implanted surface. The solution to the problem is to implant the target several times at <50 keV of energy. To minimize the un-filled volume, the study of simulation and calculation has been conducted. In this study a simulation using TRIM program to know how many times the target should be implanted at different energies and also the calculation of the amount of nitrogen ions that should be implanted, so that the distribution of nitrogen ions can be evenly distributed from the surface to 561 Å. From the results of simulations and calculations the results show that the target must be implanted at least 6 times implantation at energy 50 keV,40 keV, 30 keV, 20 keV and 10 keV. Under these conditions the dose that must be implanted are 7,4×1017ion/cm2, 6,44×1017ion/cm2, 4,6×1017 ion/cm2, 3×1017 ion/cm2 and 1,6×1017 ion/cm2. The total doses and amount of nitrogen filling the implanted volume are 7,32%..